The role of SHR in risk stratification for long-term prognosis in patients with coronary artery disease: findings from a large cohort study - Xu, Wei; Wang, Xiang; Xia, Chenxi; Meng, Xuyang; Li, Yi; Zhao, Yejing; Yang, Chenguang; Feng, Baoyu; Zhao, Zinan; Wang, Fang (Frontiers in Endocrinology, 2025)
BackgroundRecently, the Stress Hyperglycemia Ratio (SHR) — which integrates acute increases in blood glucose with long-term glycemic control levels — has shown independent predictive value for adverse events in patients with acute coronary syndrome (ACS). However, the long-term prognostic significance of SHR in a broader population of coronary artery disease (CAD) remains unclear. This study aimed to explore the role of SHR in prediction of long-term prognosis of CAD.MethodsIn this cohort study, we enrolled 23,591 participants diagnosed with CAD from January, 2016, to December, 2021 in Beijing Hospital. After excluding patients lacking data, with cancers, or missing follow-ups, 7,162 patients were finally enrolled into the analyses. The SHR was calculated using the following equation: SHR = admission glucose (mmol/L)/(1.59 × HbA1c [%]-2.59). The 7,162 participants were divided into three groups based on SHR tertiles: Tertile 1 (SHR ≤ 0.72, n=2391), Tertile 2 (0.73≤SHR ≤ 0.82, n=2388), and Tertile 3 group (SHR≥0.83, n=2383). The primary endpoint was all-cause mortality and cardiovascular death (CVD), while the second endpoint was major adverse cardiovascular events (MACE). The median follow-up was 28 months.ResultsOur results suggest that SHR was significantly associated with increased risks of long-term all-cause death, CVD death, and MACE. The Kaplan-Meier curves revealed that the highest tertile (T3) group had the highest risk of all-cause death, CVD death, and MACE, while the lowest tertile (T1) group had the lowest risk (all log-rank P < 0.05). After adjusting risk factors, the results of cox regression analyses showed that SHR was significantly associated with all three outcomes (all P < 0.05). For all-cause death, SHR was associated with an increased risk of all-cause death in the fully adjusted model (Model 3: HR = 2.52, 95% CI: 1.57 – 4.05, P < 0.001). Compared to the lowest tertile (T1), participants in the highest tertile (T3) had a likely higher risk of all-cause death (HR = 1.40, 95% CI: 1.05 – 1.87, P = 0.021). SHR also demonstrated a positive association with CVD death (Model 3: HR = 2.87, 95% CI: 1.22 – 6.76, P = 0.016), and participants in T3 had a significantly higher risk of CVD death compared to T1 (HR = 1.94, 95% CI: 1.11 – 3.40, P = 0.021). Additionally, SHR was also independently associated with MACE (Model 3: HR = 1.70, 95% CI: 1.21 – 2.38, P = 0.002). The risk of MACE was significantly higher in T3 compared to T1 (HR = 1.21, 95% CI: 1.02 – 1.45, P = 0.031). The restricted cubic spline (RCS) analysis further confirmed a positive nonlinear association between SHR and these adverse outcomes (all-cause death, CVD death, and MACE) and exhibited a J-shaped curve.ConclusionsSHR is significantly associated with long-term all-cause death, CVD death, and MACE in CAD patients. Our findings highlight SHR can be used as a valuable tool for long-term prognosis risk stratification in CAD, potentially influencing clinical decision-making and patient management strategies.